PCDH9 suppresses melanoma proliferation and cell migration - Zhang, Jiaojiao; Yang, Hui-Zhi; Liu, Shuang; Islam, Md Obaidul; Zhu, Yue; Wang, Zuhua; Chen, RongYi (Frontiers in Oncology, 2022)
Melanoma has dramatically increased during last 30 years with low five-year survival and prognosis rate. After bioinformatics mining, reference investigation and nutrition-melanoma-suppression study, certain genes (PCDH9, MMP2, CCND1 and RAC1) were selected. To explore the influence of PCDH9 on melanoma cells in terms of PCDH9 alteration in vitro, PCDH9 was interfered and overexpressed by lentivirus. The immunohistochemical result showed lower PCDH9 expression in melanoma tissue than in normal skin or/and pigmented nevus tissue. The assessment of PCDH9 influences on melanoma cells were processed by cell viability, apoptosis, cell cycle and wound healing assay, whose results were consistent with IHC. The study showed that: 1) the alteration of PCDH9 has negative correlation with MMP2 and RAC1, while had positive with CCND1 (Cyclin D1) and apoptosis; 2) increase of PCDH9 could suppress melanoma cells and inhibit migration, but not exert significant effects on cell cycle; 3) interestingly, IHC also showed lower PCDH9 expression in melanoma tissue with main expression in cytoplasm. In conclusion, alteration of PCDH9 expression could influence melanoma cells.